Performance of prefabricated sewage treatment plants at a military academy - Mohd Asri Md Nor; Nabihah Mohd Nazir; Shahrul Sahusi; Zuliziana Suif (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents the results of performance monitoring of wastewater treatment systems installed at Universiti Pertahanan Nasional Malaysia (UPNM). UPNM is a military-based university located in Sungai Besi Camp, Kuala Lumpur, Malaysia. As the university expands, new buildings were constructed and new prefabricated sewage treatment plants (STPs) were installed. Effluent of these STPs were monitored and compared with required standards. Effluent samples were collected from three STPs for three months and tested for parameters of pH, temperature, biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen, nitrate, and phosphorus. The results were then compared with the standard B of the Environmental Quality (Sewage) Regulations 2009. Diurnal fluctuation of the effluent quality was also studied. From the data observed, it shows that the performance of the wastewater treatment plant is good. The effluent quality also achieved the allowable standards set by the authority. Maximum diurnal fluctuation was observed for COD which fluctuated between 18 and 52 mg/L which is still lower than standard B for COD effluent limit of 200 mg/L.